A Portable Cruising Speed Net: Expanding Global Collection of Sea Surface Plankton Data - von Ammon, Ulla; Jeffs, Andrew; Zaiko, Anastasija; van der Reis, Aimee; Goodwin, Deb; Beckley, Lynnath E.; Malpot, Emmanuel; Pochon, Xavier (Frontiers in Marine Science, 2020)
Plankton are central to planetary ecology, generating 50% of Earth’s atmospheric oxygen and forming the largest system of interconnected life at the base of the marine food chain. Yet, current oceanographic models aimed at predicting global climate change lack high-resolution biological data, emphasizing the need for innovative approaches to collect plankton biodiversity and distribution data over larger spatial, temporal, and taxonomic scales. The significant number of boats, ranging from small sailing yachts to large commercial vessels, that ply the world’s oceans every day could help scientists collect thousands of valuable plankton samples. Traditional Plankton Nets (TPN) are not suited to the speed of a recreational craft cruising in the high seas (i.e., at speeds >2 knots). We developed and validated the efficiency of a lightweight, easily deployable Cruising Speed Net (CSN) that enables the collection of ocean surface micro- and mesoplankton at speeds up to 5 knots. Field testing was conducted during two distinct research cruises along coastal and oceanic latitudinal gradients (SSV Robert C. Seamans in New Zealand and RV Investigator in the south-east Indian Ocean). DNA metabarcoding performed on the collected plankton samples showed the TPN and CSN yielded identical diversity at low speed, with the CSN also effective at higher speed for characterizing latitudinal distribution of plankton communities. The CSN represents a valuable new tool for expanding the global collection of plankton data.